Interferences and Events On Epistemic Shifts in Physics through Computer Simulations - Dippel, Anne; Warnke, Martin (meson press, 2017)
Computer simulations are omnipresent media in today's knowledge production. For scientific endeavors such as the detection of gravitational waves and the exploration of subatomic worlds, simulations are essential; however, the epistemic status of computer simulations is rather controversial as they are neither just theory nor just experiment. Therefore, computer simulations have challenged well-established insights and common scientific practices as well as our very understanding of knowledge. This volume contributes to the ongoing discussion on the epistemic position of computer simulations in a variety of physical disciplines, such as quantum optics, quantum mechanics, and computational physics. Originating from an interdisciplinary event, it shows that accounts of contemporary physics can constructively interfere with media theory, philosophy, and the history of science.